Crisis Experience and the Deep Roots of Covid-19 Vaccination Preferences - Ekaterina Borisova; Klaus Gründler; Armin Hackenberger; Anina Harter; Niklas Potrafke; Koen Schoors (Center for Economic Studies and ifo Institute (CESifo), 2023)
We examine the deep roots of preferences for vaccination against COVID-19, moving beyond proximate factors which can only account for part of the observable heterogeneity in the willingness to get vaccinated. Our model on experience-based learning predicts that exposure to past disruptive crises increases individuals' willingness to acquire and take a promising remedy when new crises occur. Using micro-level data on vaccination preferences for individuals from 19 countries, we find strong evidence for our prediction. We investigate the role of competing vaccines exploiting original geocoded survey data from Russia. Consistent with our theory, past crisis experience decreases vaccination willingness when individuals have learned to distrust the effectiveness of government administered remedies.
Keywords: H12; H51; I12; I15; I18; 330; Covid-19 vaccination; vaccination preferences; crisis experience; experience effects; survey data; geocoded data